2016
DOI: 10.1002/jso.24224
|View full text |Cite
|
Sign up to set email alerts
|

Importance of margin width in breast‐conserving treatment of early breast cancer

Abstract: An overall low rate of IBTR was observed. A final positive margin was associated with a more than twofold risk of IBTR. There was no evidence for better local control with wider margins, but the data were insufficient to show whether narrow margins were as good as wider negative margins in terms of local control. J. Surg. Oncol. 2016;113:609-615. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 41 publications
0
22
0
1
Order By: Relevance
“…37,39,40 Early results from a large Danish study of 11 900 patients found no evidence of improved local control by margin depth. 41 A previous study found that patients treated without a boost (usually because of a large excision specimen or a negative re-excision) had no increase in the risk of local recurrence compared with patients who did receive a boost. 31 In practice, the surgeon can assist boost planning by placing titanium clips at the excision borders.…”
Section: Discussionmentioning
confidence: 98%
“…37,39,40 Early results from a large Danish study of 11 900 patients found no evidence of improved local control by margin depth. 41 A previous study found that patients treated without a boost (usually because of a large excision specimen or a negative re-excision) had no increase in the risk of local recurrence compared with patients who did receive a boost. 31 In practice, the surgeon can assist boost planning by placing titanium clips at the excision borders.…”
Section: Discussionmentioning
confidence: 98%
“…Then an alternative surgical management for early breast cancer has emerged, named as breast conserving surgery (BCS), where instead of removing the entire breast, only the tumour with a cuff of normal tissue all around is removed. [9][10][11][12] The contour and cosmetic appearance of the breast is preserved. Axillary nodes are addressed through a separate axillary incision.…”
Section: Introductionmentioning
confidence: 99%
“…1 Despite this equivalence in outcome, positive surgical margins following BCT have been associated with a significantly increased risk of local recurrence. 26 Margin status has become a critical factor in the management of patients undergoing BCT, and the controversy surrounding the importance of negative margins and the absence of definitive guidelines have led to a wide variability in surgeon practice regarding the threshold for re-excision. In 2002, the landmark National Surgical Adjuvant Breast and Bowel Project (NSABP) B-06 trial prompted the widespread acceptance of BCT and considered no tumor cells at the inked specimen margin to be a negative margin, but this definition failed to translate universally into practice until recently.…”
Section: Introductionmentioning
confidence: 99%
“…Prior to early 2014, up to 60% of patients underwent re-excision for management of margins, and adequacy of pathologic margin status remained surgeon-specific and highly ambiguous, ranging from no tumor at the inked margin to margin widths > 5 mm. 611 In May 2014, the Society of Surgical Oncology (SSO) and American Society of Radiation Oncology (ASTRO) published a consensus statement recommending that the definition set forth in NSABP B-06 become the global standard for an adequate margin in breast-conserving surgery (BCS) in women with stage I/II disease undergoing adjuvant whole breast radiation therapy. 12 Drawing upon a meta-analysis of 33 studies, a multidisciplinary consensus panel determined that no significant differences in local recurrence were present regardless of factors such as patient age, tumor biology, or presence of an extensive intraductal component in the setting of “no ink on tumor”.…”
Section: Introductionmentioning
confidence: 99%